Con Aprecio / With Appreciation: Pushing Beyond the Boundaries of Possibility in Educational Professional Development (LEARNing Landscapes, 2015)
The need for relevant, continuous, and restorative professional development is evident at all levels of teacher education. As teachers teaching teachers and educators educating educators, we aspire to implement meaningful, sustaining, learning experiences that make a difference in the lives of children, families, educators, and communities. This reflective testimony calls us to consider the funds of knowledge and example of our colleagues in the tireless quest to embody and enact civil rights law, and move beyond the boundaries of possibility in educational professional development to actualize educational equity and social justice.
Keywords: professional development; educational equity; social justice; change